PENGARUH CUSTOMER RELATIONSHIP MARKETING, KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN PADA PT. HADJI KALLA DI MAKASSAR - Arham Arham; Andi Irfan; Yusram Adi (JURNAL LENTERA BISNIS, 2025)
This study aims to determine and analyze the influence of Customer relationship marketing and service quality on customer satisfaction, the influence of Customer relationship marketing, service quality and satisfaction on customer loyalty, the influence of Customer relationship marketing and service quality on customer loyalty through satisfaction at PT. Hadji Kalla in Makassar. This study uses a quantitative approach, with data collection techniques through questionnaires, the population taken is customers of PT. Hadji Kalla in Makassar which is determined as many as 95 respondents using path analysis. The results of the study found that customer relationship management and service quality have a positive and significant effect on customer satisfaction at PT. Hadji Kalla in Makassar, then customer relationship management, service quality and satisfaction have a positive and significant effect on customer loyalty at PT. Hadji Kalla in Makassar. The results of the mediation test obtained findings that customer satisfaction can mediate the influence of customer relationship management and service quality on customer loyalty at PT. Hadji Kalla in Makassar.